Effect of six weeks of Total Body Resistance Training (TRX) and oral intake of aqueous extract of mango leaves (Mangifera indica) on serum TNF-α level and body mass index in non-athletic men - Omid Mohammaddoost; Fateme Shabkhiz; Ali Akbar Nejad (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: The increase in inflammatory markers, including TNF-α, contributes to the development and progression of cardiovascular complications. This study aimed to investigate the effects of six weeks of total body resistance training (TRX) and oral consumption of aqueous extract of mango leaves (Mangifera indica) on serum TNF-α level and body mass index (BMI) in overweight and obese non-athletic men. Methods: In this semi-experimental study, 48 overweight and obese non-athletes aged 20 to 25 years were randomly assigned to four groups: control, mango leaf extract, exercise + placebo, and exercise + extract. For six weeks (three sessions per week), participants engaged in total body resistance training (TRX) and consumed aqueous mango leaf extract (two capsules of 500 mg per day). Serum TNF-α level were measured 24 hours before the first session and 48 hours after the last training session using the ELISA method. Additionally, measurements for weight, BMI, and waist-to-hip ratio (WHR) were recorded. Results: After six weeks of intervention, serum TNF-α levels significantly decreased in the exercise + placebo, exercise + extract, and mango leaf extract groups compared to pre-test values (P = 0.0001). In the post-test, both the exercise + extract and exercise + placebo groups, along with the mango leaf extract group, demonstrated a significant reduction in TNF-α levels compared to the control group (P < 0.001). Furthermore, body weight, BMI, and WHR were significantly reduced in the exercise + placebo and exercise + extract groups compared to the mango leaf extract and control groups (P < 0.001). Conclusion: Six weeks of TRX training combined with the consumption of mango leaf extract may effectively reduce inflammatory markers such as TNF-α, as well as decrease BMI and WHR in young overweight and obese non-athletes. These findings suggest valuable insights for implementing effective exercise programs aimed at addressing obesity in young men.